Penyebab Langsung (Immediate Cause) yang Mempengaruhi Kejadian Stunting pada Anak - Bagus Pratama; Dian Isti Angraini; Khairun Nisa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Short stature (stunting) is a nutritional problem that has implications on children’s growth problems. The consequences to the children are having lower length or height comparing to other children at their age. The results of nutritional status measurement show that less than -2 to -3 of standard deviations (stunted) and less than -3 of standard deviations (severely stunted). This condition occurs because the golden period is not achieved in the first thousand days of a child's life. Stunting can be caused by various factors like the conditions of mother or prospective mother, fetal period, infancy period or on the first thousand days period of life. Direct actors that influence stunting such as inadequate food intake and infectious disease, or the child's health status.